2018
DOI: 10.6028/nist.ams.100-14
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of solidification phases in Cr-Ni stainless steel alloys manufactured by laser based powder bed fusion process

Abstract: The microstructure and strength of chromium-nickel (Cr-Ni) stainless steel alloy parts is highly dependent on the chemical composition of the material and the thermal cycling it experiences during each processing step. This is particularly true when utilizing a laser powder bed fusion (LPBF) process to create the part. LPBF is an additive manufacturing (AM) process that quickly scans a laser over thin layers of powder to melt and solidify the powder to create the part. This results in rapid heating and cooling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…SP-induced changes in the surface layer, as well as changes in the microstructure, can potentially affect the corrosion resistance of steel. During cold processing, a transformation of metastable austenite into martensite and intermediate carbides like Fe 3 C called "Martensitic stress-induced transformation" (MIST) can occur [36], which can affect corrosion resistance. One of the dangers during SP is the potential penetration of burnishing medium particles into surfaces, thus reducing or increasing corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…SP-induced changes in the surface layer, as well as changes in the microstructure, can potentially affect the corrosion resistance of steel. During cold processing, a transformation of metastable austenite into martensite and intermediate carbides like Fe 3 C called "Martensitic stress-induced transformation" (MIST) can occur [36], which can affect corrosion resistance. One of the dangers during SP is the potential penetration of burnishing medium particles into surfaces, thus reducing or increasing corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the (alpha + gama) phase appear at temperature 740 o C, which is the ratio of the alpha phase dominates the gamma phase because it is close to the alpha zone, and, at this temperature the size of the particles is larger, therefore it is characterized by greater ductility and lower hardness. As for the martensitic stainless steel, the martensite phase (cementite + ferrite) which contains cementite needles, which are by nature hard and needle-shaped, and have a lower ductility due to the phase shift from (cementite + ferrite + perlite), due to the (austenite + ferrite) phase, which led to decrease in the hardness value with increase in the ductility [17]. From the obtained results, it was concluded that the temperature and load have a direct relationship in the two samples for short time creep test.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, N 2 gas is more typically selected for the less-reactive alloys, such as stainless steels and Ni alloys [165,170]. The N 2 gas employed in the LPBF may produce nitrogen-based compounds in as-built microstructures, which can improve corrosion resistance and alter mechanical properties [171][172][173]. Therefore, shielding gases must be carefully selected based on their application.…”
Section: Process Atmospherementioning
confidence: 99%